Abstract in Undergraduate Thesis: a Study of Linguistic Realizations of Rhetorical Moves and Thematic Patterns of Indonesian EFL Students - Danang Satria Nugraha; Concilianus Laos Mbato (Makassar State University, 2022)
Abstract. In academic writing, an abstract is the most important initial part of a publication. Besides being substantive, an abstract is a reflection of the quality of the publication. Based on fifty abstracts from Indonesian undergraduate students’ publications in two departments, this study aimed to explore these questions: (1) how do Indonesian undergraduate students apply the rhetoric moves in their research abstracts and (2) how do Indonesian undergraduate students apply the thematic patterns in their research abstracts? In doing so, Paltridge’s (2012) Thematic Progression and Swales’s (2004) CARS model were adopted. The results showed at least three obligatory rhetorical moves in the abstract written by Indonesian undergraduate students, viz., (a) situating the research, (b) describing the methodology, (c) and summarizing the findings. The results also indicated that both linear and constant thematic patterns tended to be predominantly utilized by students. This was evident in certain linguistic features including grammatical subjects, verb tense, and voice. This study provides practical and pedagogical implications for lecturers and undergraduate students involved in academic writing, and suggestions for future research.Keywords: Research Abstract, Rhetoric Moves, Thematic Patterns, Indonesian Undergraduate Students